Clinical Efficacy of Kedo S Square Files versus Manual K Files in Root Canal Preparation of Deciduous Molars: A Randomised Clinical Trial - Bala Anusha Durairaj; Prathima Gajula Shivashankarappa; Kavitha Muthukrishnan; G Ezhumalai; Eswari Ramassamy (Journal of Clinical and Diagnostic Research, 2023)
Introduction: The conventional approach to root canal preparation in primary molars involves hand instrumentation. However, the disadvantage of longer instrumentation time poses a challenge for dentists treating paediatric patients. As a solution, rotary file systems have been introduced to reduce chairside time and improve patient cooperation. Among the various rotary file systems available, the "Kedo S Square" rotary files are exclusive single files made of Nickel-titanium (NiTi), offering increased flexibility and variable taper to adapt to the curved canals of deciduous molars. Aim: To assess and compare the instrumentation time and obturation quality of rotary “Kedo S Square” files with manual K files in deciduous molars. Materials and Methods: This randomised clinical trial was conducted from July 2022 to February 2023 included 40 primary molars from four to six-year-old children requiring root canal therapy. The teeth were evenly allocated to two groups: Group 1 underwent instrumentation using “Kedo S Square” files, while Group 2 underwent instrumentation using manual K files. The instrumentation time was recorded, and post-treatment radiographs were taken to evaluate the quality of obturation by a single-blinded investigator. Statistical analysis included the Independent t-test, Levene’s Test for Equality of Variances, Chisquare test, and Fisher’s-exact test. Results: The use of Kedo S Square files resulted in significantly less instrumentation time (p<0.001) with a mean time of 3.91±1.462 minutes. There was no statistically significant difference in obturation quality between the two groups, with a p-value of 0.427. Conclusion: Kedo S “Square” files demonstrated comparable obturation quality with shorter instrumentation time compared to manual K files in root canals of primary molars.